The Invisible Enemy: Representing Labour in a Corporate Media Order - Bekken, Jon (Javnost-The Public, 2005)
Substantial research documents the central role of the U.S. media in delegitimising and marginalizing the labour movement. U.S. journalists cover labour only rarely, and then through the prism of a “public” interest frame that submerges class relations, privileges commodities over the workers who produce them, and implicitly supports capital over the workers whose actions threaten to (or do) disrupt the ordinary flow of commerce. This coverage is deeply rooted in the patterns of thinking taught in academic journalism programs. Leading American journalism textbooks rarely suggest seeking information or comment from labour leaders or union members, even for stories in which unions would be deeply involved. When textbooks ask students to write articles about hiring freezes and lay-offs based solely on press releases or “notes” from news conferences by corporate officials, students are being taught a clear lesson about whose perspective matters. Journalism textbooks largely ignore the vast majority of the population – those who must work for a living. Workers and their unions exist only on the margins, as a disruptive force that inconveniences the general public. That reporters trained in this way go on to ignore labour concerns and perspectives in their own reporting is hardly surprising.